Comparison of Lighting Efficiency (Led-CFL) based on Environmentally Friendly Technology - Anisah, Siti; Fitri, Rahmadhani; Taro, Zuraidah; Wijaya, Rian Farta (Journal of Applied Engineering and Technological Science (JAETS), 2022)
Light bulb waste is categorized as non-organic waste which cannot be decomposed in nature and has the potential to damage the environment. Currently the production of light bulb waste reaches 4.50% of the total waste production per day. These conditions require a solution to reduce the amount of waste produced by light bulbs. This paper aims to discuss the recycling technology used for light bulb waste, so that the waste can be reused as recycled and environmentally friendly lighting lamps. The method used in this study refers to an environmentally friendly concept, namely, designing lighting lamps using waste light bulbs that are no longer used. The design product is designed exactly the same as the previous product from the manufacturer, then proceed with testing in the laboratory to determine the electrical parameters and the amount of lumens produced. From the results of the research conducted, it can be seen that the results of the design of recycled lighting lamps have a decrease in lumens value for CFL types by 7%, LED by 8%, the durability and lifespan of light bulbs are reduced by CFL types by 32%, LED types by 30%, the results of the design recycled